Kontribusi Ekstrakulikuler Sebagai Penyokong Kemajuan Pondok Pesantren Darul Falah Aek Songsongan - Sartika Alpianti Manurung; Raudhatul Jannah; Mutia Syahdina; Muhammad Wildan Fikri Azkia; Sahkholid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Nowadays, many Islamic boarding schools have been found as a place to pursue education in the frame of Islam like mushrooms in winter. One of them is Darul Falah Islamic Boarding School. The famous name Darul Falah to various regions certainly cannot be separated from the roles and ways of various parties, in the form of the efforts of the asatidz and the contribution of students combined with the utilization of existing resources, such as extracurricular activities. This research has the aim of knowing how much extracurricular roles and their influence on the development of Pondok Pesantrean Darul Falah. The method used in this research is qualitative method, through interviews and literature review as data collection techniques, while the data analysis used is descriptive statistics. The results of this study indicate that, in fact, extracurricular activities are very helpful and have a positive impact on the development of Darul Falah Islamic Boarding School. This is evidenced by several things. Although it is not a mandatory program, extracurricular activities play an important role in the development of Pesantren Darul Falah.